The role of grit and parent-child communication in career adaptability - Wibowo, Doddy Hendro; Ambarwati, Krismi Diah; Crescenzo, Pietro (Psikohumaniora: Jurnal Penelitian Psikologi, 2020)
The transition period from school to the world of work is a critical time that affects determining one's career. This study aims to examine the role of grit and parent-child communication in students’ career adaptability. Using a purposive sampling technique, the study involved 218 High School (SMA) students and 124 Vocational High School (SMK) students in Salatiga, Indonesia. The measurement instruments used in the research were the career adaptability scale, grit scale, and parent-child communication scale. The results show that the R-value was .595 and the adjusted R squared (R2) value was .354. The significance value generated from the regression test was .000 (p<.01). Based on the calculation results, it can be concluded that grit and communication between parents and children together play a significant role in career adaptability. The research implication is that students’ grit and effective parent-child communication should be developed to improve career adaptability.